Efektifitas Pelatihan Australasian Triage Scale terhadap Pengetahuan Perawat Unit Gawat Darurat dalam Melakukan Triase - Artanti, Suci; Haryatmo, Sapto (STIKES Ngesti Waluyo, 2022)
Triage is a clinical risk management system that is very important in helping patients in the Emergency Room. However, in the hospital there is frequent rotation or transfer of staff between units as well as promotions, so that sometimes competent and experienced nurses are replaced by other, less experienced nurses. The nurse's ability to carry out triage must also be maintained so that they are able to act properly according to the specified procedure. This study aims to determine the knowledge of Emergency unit nurses in conducting triage and to determine the effectiveness of the Australasian Triage Scale training in increasing the knowledge of emergency unit nurses in conducting triage. The research method used was quasi-experimental with a one group pre test post test design approach. Sampling was carried out using a purposive sampling technique with a total of 29 nurses as respondents. The results showed that the average level of knowledge before training was 41.03 and after training was 94.14. Data analysis using the t-test obtained the t value (11.1493) > t-tab (2.048). There is a significant relationship between triage training and the level of knowledge of ED nurses in conducting triage. Triage training for nurses can become a hospital program to maintain the quality of nurses in providing services in the Emergency Unit.